2013
DOI: 10.1186/1472-6920-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Role of SimMan in teaching clinical skills to preclinical medical students

Abstract: BackgroundSimulation training has potential in developing clinical skills in pre-clinical medical students, but there is little evidence on its effectiveness.MethodsTwenty four first year graduate entry preclinical medical students participated in this crossover study. They were divided into two groups, one performed chest examination on each other and the other used SimMan. The groups then crossed over. A pretest, midtest and post-test was conducted in which the students answered the same questionnaire with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 9 publications
3
38
1
Order By: Relevance
“…Also [12] in a study about role of SimMan in teaching clinical skills as CPR demonstrated that there was a significant improvement in the students' knowledge and competence to perform CPR. While this was in disagreement with [13] in their study about Comparing two training methods for CPR skill who stated that there is no statistically significant difference between the mean scores of the total questions regarding knowledge assessment for both groups before and after training.…”
Section: Effect Of Educational Program For Cardiopulmonary Resuscitatcontrasting
confidence: 44%
“…Also [12] in a study about role of SimMan in teaching clinical skills as CPR demonstrated that there was a significant improvement in the students' knowledge and competence to perform CPR. While this was in disagreement with [13] in their study about Comparing two training methods for CPR skill who stated that there is no statistically significant difference between the mean scores of the total questions regarding knowledge assessment for both groups before and after training.…”
Section: Effect Of Educational Program For Cardiopulmonary Resuscitatcontrasting
confidence: 44%
“…15 In our study, the students had better understanding of the interrelationship between surgical placements and implant restoration with clinical experience. 15 In our study, the students had better understanding of the interrelationship between surgical placements and implant restoration with clinical experience.…”
Section: Agreement Responses Of Test and Control Groups With And Wimentioning
confidence: 95%
“…9,10 Challenges identified in establishing implant instruction in predoctoral dental education are cost for implementation, limited funding, patient availability, and limited time in the curriculum. 15 To resolve this problem, instructional methods slowly evolved to incorporate a combination of didactic and simulation training, thereby linking knowledge with clinical practice. 14 In medical education, Swamy et al found that the transition from didactic training to clinical training was a major source of stress for students.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation has the advantage of introducing students to serious clinical conditions in a standardized and non-threatening manner2 without involving actual patients and provides an environment for students to gain practice teaching,48 which also increases their knowledge retention 9. The benefits of simulation in medical education have been well documented 2,10,11. However, simulation training requires considerable resources, not the least of which is faculty time required for preparation and delivery.…”
Section: Introductionmentioning
confidence: 99%